Paper Boat in India: Beating the Giants - Sharma, Seema; Juneja, Aditya; Lakhiwal, Akshat; Tantia, Ankur (Prabandhan: Indian Journal of Management, 2016)
The beverage industry in India is growing as the income levels of the people are rising. Also, more and more people are becoming health conscious due to their lifestyles issues. In such a scenario, offering affordable and healthy juice drinks with traditional flavours by Hector Beverages has been a welcome move in the market. This brand, known as Paper Boat, targets the younger generation, and has been growing by leaps and bounds due to innovative and traditional flavours. The objective of this case study was to highlight the growth of this indigenous brand, identify the challenges and strengths, and to discuss expansion strategies. The key finding is that the USP of Paper Boat in this product category among the presence of giant players is not pricing, but the emotional connect. It can be concluded that the brand, targeting a correctly identified profitable niche, is expected to rise fast in the future with a better distribution network and appropriate communication strategies.